Evaluating the Effectiveness of the Forehand Stroke for Beginners in Tennis - ناصر ناهد; كفا عزيز; دبيلة علي (Latakia University Journal -Medical Sciences Series, 2021)
This study aimed at evaluating the effectiveness of the forehand in winning the tennis match among beginner players in Syria. The analysis of data and video records of the matches witnessed in the "Dubaila Tennis Academy" open tournament held in the Sports City in Lattakia in March 2020. The descriptive analytical approach was used. As a general method of research, data were collected for 20 matches, from 4 different categories, from beginner players, which are men and women, in addition to males, the females which are under 12 years old. The results were as follows: 67.75% of the points gained during the match was through the forehand, which played an important role in achieving victory, as well as the large number of errors committed in this skill affects the result of the match. The research recommends conducting subsequent studies to find out the reason behind the ineffectiveness of this strike sufficiently for beginner players, despite the fact that the percentage of its use is very large despite the large number of direct errors, as the percentage of the average direct errors reached 76.63%. This result also prompts us to search to find an organized approach to learning this Skill.